Metode Bahasa Isyarat Dalam Baca Tulis Al-Qur’an Untuk Anak Tunarungu di Kawasan Minoritas Muslim Papua - Anisa Eka Oktavia; Evie Syalviana; Fardan Abdillah; Syahrul Syahrul (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of the sign language method in reading and writing the Koran for deaf children in Muslim minority areas in Papua. This type of research is Experimental with Pre-Experimental design, using the One Group Pre-test Posttest Design design model. The sample in this study were 5 people with purposive sampling technique. Methods of data collection using tests, interviews, observation and documentation. Meanwhile, to analyze the data using the normality test Shapiro Wilk Test, test the validity of the content by the lecturer as an expert validator and test the Wilcoxon Signed Rank Test hypothesis. The results showed that the value of the pretest was 125 and posttest was 298 and experienced an increase of 138.40% and the results of the hypothesis test were 0.042 <0.05. Based on the results of the explanation above, it shows that the sign language method has an effect on the reading and writing of the Qur'an for deaf children in the Muslim minority area of ​​Papua..